Dampak Perdagangan Bebas Bagi Ekspor Produk Tuna dan Cakalang Indonesia - Angelica Cristy; Annisa Fitri Hartanti; Atelia Zahrah Kurniawan; Mohammad Zein Saleh (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The open trading system without restrictions, known as free trade, allows for increased product competitiveness in international markets. Tuna and skipjack commodities are Indonesia's flagship products and play a significant role in fisheries exports. This study investigates the impact of free trade on tuna and skipjack exports, identifies challenges, and explores appropriate management strategies. The findings reveal that Indonesia faces challenges such as global competition, threats to the sustainability of marine resources due to overfishing, and demands to meet international standards. However, free trade offers opportunities to expand markets and reduce tariff barriers. The use of technology, supply chain digitalization, and innovation are crucial to enhancing efficiency and product competitiveness. To sustain marine resource conservation and maintain Indonesia's position as a leading tuna producer globally, the government must implement regulations and collaborate with industry stakeholders. Through a comprehensive strategic approach, Indonesia can preserve marine ecosystem sustainability while continuing to increase the contribution of tuna and skipjack exports to the national economy.